Le vie della mimesis tra teatro e musica in Jean-Jacques Rousseau: storia di un apparente paradosso - Maria Semi (University of Bologna, 2021)
Theatre and opera in Rousseau’s works deserve radically different treatments. Although the citoyen de Génève recognizes interest and imitation as common principles to both forms of art, the nature of theatrical and musical imitation sets them apart. The article draws on many writings of Rousseau to show how considerations about the role played by pity and imagination in the development of human history stand in the background to the author’s analysis of imitation and it singles out the peculiar relationship between music and language as crucial to the distinction between the moral effects of theatre and music.